2017
DOI: 10.1002/hep4.1074
|View full text |Cite
|
Sign up to set email alerts
|

Rapid changes in peripheral lymphocyte concentrations during interferon‐free treatment of chronic hepatitis C virus infection

Abstract: Treatment of chronic hepatitis C virus infection with direct acting antivirals results in a rapid decline in viral load and markers of hepatic inflammation, including serum CXCL10 concentration, which is followed in most cases by a sustained virologic response. Whether parallel changes of significance occur in the cellular composition of peripheral blood is relatively unknown. We hypothesized that longitudinal characterization of peripheral blood during treatment would provide insight into cellular migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 25 publications
3
43
0
2
Order By: Relevance
“…In our study, after direct‐acting antiviral treatment, we found a significant decline in markers of T‐cell activation. A previous study also reported a decline of T‐cells CD38+HLADR+ expression in chronic HCV patients, after interferon‐free treatment …”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In our study, after direct‐acting antiviral treatment, we found a significant decline in markers of T‐cell activation. A previous study also reported a decline of T‐cells CD38+HLADR+ expression in chronic HCV patients, after interferon‐free treatment …”
Section: Discussionmentioning
confidence: 71%
“…A previous study also reported a decline of T-cells CD38+HLADR+ expression in chronic HCV patients, after interferon-free treatment. 36 The immunophenotypic analysis was performed only in Group ≥F3, since it is known that the chronic immunosuppressive therapy, as administered in patients in Group LT + ≥F2, could impact on the CD38 expression on T-cells. Indeed, it has been reported that CD38 expression on T-cells is under-expressed after anti-rejection therapy, and its determination has been proposed as assay to be used routinely to quantify the level of immunosuppression in clinical practice.…”
Section: Factors Associated With Hcv Relapsementioning
confidence: 99%
“…In this study, we used a unique collection of paired liver biopsies from patients treated with DAA therapy to ask how a broad array of intrahepatic immune cellular populations change during DAA therapy, and explored whether there were associations with treatment outcome. We consider these findings in the context of prior work showing that multiple peripheral cellular populations change rapidly after DAA therapy, which we hypothesized was due to efflux of intrahepatic lymphocytes as well as reduced de novo migration …”
Section: Introductionmentioning
confidence: 79%
“…We consider these findings in the context of prior work showing that multiple peripheral cellular populations change rapidly after DAA therapy, which we hypothesized was due to efflux of intrahepatic lymphocytes as well as reduced de novo migration. 16…”
Section: Introductionmentioning
confidence: 99%
“…The reactions can be explained by direct immunological drug effects or by immuno‐infectious changes (“reconstitution” syndrome with DAAs). 7,10 The latter is a hypothesis, which could be supported based on some studies that highlighted the relation between HCV viremia in T‐cell activation and the roles of interferon‐gamma (IFN‐γ), interleukin (IL)‐17, and IL‐22 producing T helper (Th1, Th17, and Th22) cells in HCV infection . These cytokines can have a significant decrease after DAA therapy, and some are also a target for psoriasis treatment.…”
Section: Characteristics Of Clinical Casesmentioning
confidence: 96%